Exploring murE protein inhibitors of Tropheryma whipplei through pharmacoinformatic approaches incorporating solubility-enhancing formulation insights - Basharat, Zarrin; Wei, Calvin R.; Islam, Madiha; Ahmed, Ibrar; Ogaly, Hanan A.; Al-Zahrani, Fatimah A. M.; Waheed, Yasir; Kim, Seil (Frontiers in Pharmacology, 2025)
Tropheryma whipplei the causative agent of Whipple disease, presents a diagnostic challenge due to its diverse symptomatology, including weight loss, abdominal pain, diarrhea, joint pain, fever, and occasionally neurological manifestations. Its resistance to fluoroquinolones complicates treatment further. Traditional methods for antibiotic susceptibility testing are ineffective as Tropheryma whipplei cannot be cultured in axenic media. To address this, we explored potential drug targets within its core genome as no drug targets from this bacterium have been studied so far. murE, a macrolide-resistant enzyme, emerged as a promising candidate exhibiting both resistance and drug target characteristics. We screened over 1,000 lead-like Ayurvedic compounds against the target enzyme UDP-N-acetylmuramyl-tripeptide synthetase and identified three promising candidates: (1) Ergost-5-en-3-ol (3beta,24xi), (2) [6]-Gingerdiol 3-monoacetate, and (3) Valtrate. DiffDock and GNINA rescoring yielded consistent binding strength rankings. Molecular dynamics simulations over 100 nanoseconds confirmed stable interactions with these compounds. ADMET analysis indicated low water solubility, but coupling with cyclodextrin SBE-β-CD improved solubility. None of the compounds showed hepatotoxic effects, though Valtrate exhibited AMES toxicity. Based on the favorable properties, we propose scaffold hopping and further in vitro/in vivo studies on [6]-Gingerdiol 3-monoacetate. Our findings offer potential avenues for combating T. whipplei infections, addressing the limitations posed by antibiotic resistance.